Image descriptors in angiography - Hofschen, Katharina; Geissler, Timo; Rieke, Nicola; zu Berge, Christian Schulte; Navab, Nassir; Demirci, Stefanie (Informatik aktuell, 2017)
Despite recent advances in the field of image-guided interventions (IGI), the bottleneck for Angiography/X-ray guided procedures in particular is accurate and robust 2D-3D image alignment. The conventional, straight-forward parameter optimization approach is known to be ill-posed and less efficient. Retrieval-based approaches may be of superior choice here. However, this requires salient and robust image features, which can handle the difficulties of Angiographic images such as high level of noise and contrast variance. In this paper, we investigate state-of-the-art features of the field of computer vision regarding the applicability and reliability in the challenging scenario of Angiography.
CRIS-Team Scopus Importer:2023-03-08